Inventory control as a strategic differential: application in a textile retail company - Giacomin, Carina; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2022)
This present research aims to understand and understand the inventory control and planning process as a competitive strategy that influences the market and thus its importance in companies. From the research-action methodology, the aim of the work is to analyze the stock of a retailer in the textile industry as a whole and apply, through Production Engineering tools, the control and planning in it. Being the chosen tools for application: Curve ABC and Security Stock. The company under study currently has no control in the stock, and the same held randomly and replaced when there is a signal of lack of products by sellers. In this way, the aim is to be able to verify how stock management is essential and important for an effective stock control and this is important in business strategy.